ANALISIS PENGEMBANGAN KEPEMIMPINAN SISWA DALAM PENDIDIKAN KARAKTER DI SD MUHAMMADIYAH JOGOKARIYAN MELALUI PROGRAM LEADERSHIP TRAINING - Zulfa Muthi’a Batrisyia; Ari Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The current challenge in education is to create a generation that is not only knowledgeable but also has a strong character. Muhammadiyah Jogokariyan Elementary School holds a student leadership development program through leadership training. This program is designed for an annual program in a work meeting by the principal, teachers, and committee. This program is structured in stages from grade 1 to grade 6 which contains elements of student leadership training from an early age. This study aims to determine the planning, implementation, supporting factors, and inhibiting factors of student leadership development in character education at Muhammadiyah Jogokariyan Elementary School through a leadership training program. The research method uses a descriptive qualitative approach with quantitative analysis, with data collected through observation, interviews, and documentation. The data sources obtained are from the principal, teachers, and students as research subjects. The results of the study indicate that 1) the implementation of the student leadership development program in character education reviewed through the leadership training program includes: the leadership values ​​of responsibility, courage, and empathy. 2) the character values ​​developed reviewed through the leadership training program include: the character values ​​of discipline, religiousness, independence, and caring. 3) supporting factors for the analysis of student leadership development in character education include: a) the role of parents, b) the role of peers. 4) There are three factors inhibiting the analysis of student leadership development in character education, namely: a) the role of the family (parents), b) the role of peers, c) gadget factors.